Lightweight block ciphers: A comparative study - Salim, Sufya; Taha, Imad (Design for Scientific Renaissance, 2012)
Although the AES is an excellent and preferred choice for almost all block cipher applications, it is not suitable for extremely constrained environments such as RFID (Radio-Frequency IDentification) tags and sensor networks. Therefore lightweight cryptography has become very vital and a strong demand in designing secure lightweight cryptographic modules is required. This paper meant to be a reference (for the cryptographic designers) on the lightweight block ciphers. It starts by doing a survey to collect the latest proposed ciphers, then to study them in terms of their algorithms specifications, hardware implementation and attacks. Finally, after the explanation and comparison, this research can be the basement for starting point to improve the lightweight block cipher in many directions like number of clock cycle, size of memory, number of Chosen Plaintext, GE, throughput and attacks. Also, this paper is under our investigation